Pharmacological Research of Loravit Suppositories - Iryna, V. Herasymova (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: The work represents the data about the worldwide spread age of allergic diseases both among adult and childish population. The given information is released according to the literary data analysis, including the WHO data. By studying these literary data, we prove the actuality of new antiallergic medicines creation, particularly, in pediatrics. Materials and Methods: The experimental part represents the study results of antihistamine activity, acute toxicity, and safety of new drug for the children’s allergic disease medication. The research has been using pharmacological, physiological, and instrumental methods alongside the mathematical statistics method. Results and Discussion: As a result for investigations, we defined, that Loravit, a new antihistamine drug, prevents the conglomeration of homocytotropic antibodies, suppresses the mastocytes degranulation, which speaks of its manifested antiallergic activity. While investigating the drug’s acute toxicity, the Loravit test sample in 5000 mg/kg dose was defined not to cause the animals death and influences the mass coefficients of internal organs, which proves the absence of meaningful test sample toxicity in the given dose, which characterizes it as non-toxic. Summary: By the investigation of Loravit suppositories pharmacological activity, its test samples were proven to obtain a manifested antiallergic activity. By the results of toxicological investigations, the new loratadine hydrochloride-based drug is considered to be mostly non-toxic (toxicity Class V, LD50 >5000 mg/kg) according to the general toxicity classification. The results of investigations allow to consider the developed drug to be perspective for further production and market implementation.